La política y su grandeza sombría. Notas sobre realismo político de Raymond Aron. - Jerónimo Molina Cano (Revista Enfoques, 2009)
According to the author, the notion of political realism should be reserved to the political writer that subscribes to the tradition of the primacy of politics. When it is said that those writers only contemplate politics under the optic of power, what is being done is to confuse in an interested way, political cynicism with realism. That explains many semantic mistakes in international relations. In this context, Raymond Aron is a political realist because his thesis distinguishes the primacy of politics as the presupposed in a political theory of mediation between different human orders. In this work, the author explains Aron's definition of politics through the revision of selected bibliography.